THE CORRELATION BETWEEN STUDENTS’ MOTIVATION IN READING AND THEIR READING ABILITY - Amalia, Nurvi; Erni, Erni; Azhar, Fadly (TELL - US JOURNAL, 2025)
This study investigated the relationship between students’ reading motivation and their reading ability at SMK IT Al-Izhar Pekanbaru. A quantitative correlational research design was employed. The study involved a population of 41 first-year vocational high schools students, selected through a total sampling technique. Data were collected using a validate 30-item motivation questionnaire (α = .894) and a 20-item reading test on narrative and descriptive texts (KR-20 = .860). The data were analyzed using Pearson correlation analysis in IBM SPSS Statistics 26. The results revealed a moderate, positive, and statistically significant relationship between the two variables (r = 0.363, p < 0.05), leading to the rejection of the null hypothesis. Moreover, motivation accounted for 40.45% of the variance in reading scores. The study provides empirical evidence for a substantive link between motivational factors and reading ability, supporting the principles of Self-Determination Theory (SDT) and highlighting the importance of fostering motivational strategies in English language teaching at vocational high schools.